Portal vein thrombosis before and after transjugular intrahepatic portosystemic shunt placement: An observational study (STROBE compliant). Issue 45 (November 2017) - Wan, Yue-Meng; Li, Yu-Hua; Wu, Hua-Mei; Xu, Zhi-Yuan; Xu, Ying; Yang, Li-Hong; Wu, Xi-Nan; Yang, Jin-Hui
Abstract : Abstract: Portal vein thrombosis (PVT) is common in patients with cirrhosis undergoing transjugular intrahepatic portosystemic shunt (TIPS). This study had 3-fold aims: to assess risk factors for PVT; to determine the efficacy of anticoagulant therapy; to investigate the impact of PVT on clinical outcomes in TIPS-treated cirrhosis. Between June 2012 and February 2016, 126 TIPS-treated patients with cirrhosis were enrolled and studied prospectively. Enrolled patients were screened for PVT before TIPS and at 3, 6, 12, and 24 months post-TIPS. All patients received warfarin (1.5–3.0 mg/day) or aspirin (100 mg/day) or clopidogrel (75 mg/day) post-TIPS. Results of patients with and without PVT (baseline and de novo) were compared. White blood cell (WBC) counts (odds ratio (OR): 0.430, 95% confidence interval (CI): 0.251–0.739, P = .002) and Child–Turcotte–Pugh (CTP) score (OR: 2.377, 95% CI: 1.045–5.409, P = .039) were significant baseline predictors for PVT in TIPS-treated patients with cirrhosis. Warfarin resulted in markedly greater rates of complete recanalization than aspirin or clopidogrel ( P < .05) in patients with PVT. Patients with PVT had markedly higher 2-year cumulative rates of variceal rebleeding, shunt dysfunction, hepatic encephalopathy, and hepatocellular carcinoma, and prominently lower overall survival than those without PVT ( P < .05). In TIPS-treated patients with cirrhosis, lower WBC count and higher CTP score were independent baseline predictors for PVT; patients with PVT had worse clinical outcomes than those without; warfarin may be more effective in recanalizing PVT than aspirin or clopidogrel.